Diseño del plan estrategico institucional para el centro educativo iberoamericano del canton Quevedo periodo 2012-2015 - Santamaria Zambrano, Jenny Paola (2012)
Our research is a qualitative study in which we aim to establish the importance of corporate communications, the Latin American Educational Center. Reason that we have considered the following problem: The need to improve institutional communication between human groups involved in the teaching - learning process “Iberoamerican” Education Center through design of a strategic plan aimed at achieving the goal. Concomitant with the problem arises overall goal: Design a strategic communication plan that ensures the flow of timely and relevant information to help achieve the mission and objectives of the School. Based on the hypothesis that: an institutional strategic plan that considers a training plan for principals and teachers, workshops for students, parents and school to monitor and evaluate the same improve communication between stakeholders from academia: students, teachers, managers and parents. The theoretical framework for an analysis of the New Trends in Communication in Education, approaches, and potential dangers of poor or nonexistent Educational Institutional Communication through the development of diverse and varied educational programs, seeking to implement measures that articulate effectively and efficiently to individuals in their social context. The importance for the development of the institution's general aims, principles, fundamentals, good communication goals. Also delves into a study of planning, its genesis, evolution and conceptualization, to be modeled in our strategic planning and research particularly educational strategic planning model as the most appropriate to our field of study, which allows us to address the educational institutions with the active participation of all professionals who make. In terms of methodology that covers the second chapter, is a qualitative analysis of the results obtained in order to verify the importance of strategic planning for Institutional Communication School. In this note the type of research you do the same by design because we apply field surveys, interviews and observation, using the methods: Description. - Because to continue the research process need data collection, analysis, systematization, the interpretation to reach conclusions and recommendations that allowed us to build the alternative proposal. Analytic - synthetic. - Because we allowed into an analysis of the factors affecting the problem and thus find alternative solutions. Universe was taken as the various members that make up the community Educational Director of the Institution, Teachers and Parents. In the third chapter, we performed the processing and analysis of data and followed the following steps: • Scale nominal variables and ordinal type Data collection • Through tab: Survey and Interview guide. • Tabulation, analysis and interpretation of the results. • Descriptive statistics was applied • Application of SWOT Matrix • Drawing Conclusions and recommendations This analysis gotta check the hypothesis in the form qualitative, since the type of communication that has developed in the Latin American Educational Center has been operating illegally and without the application of any strategy or plan to guide their actions, and it is necessary to propose a model of Strategic Plan enable them to manage and improve institutional communication in turn provide the highest quality services that meet the demands of everyone involved in the educational work. Finally the proposal of "Designing a Strategic Plan to improve institutional communication in the teaching - learning process of the School Collaboration. In this part of the thesis presents the design of the proposal through the Education Strategic Planning model, the sequence of the respective moments that make mention in the theoretical framework, the same as after the diagnosis strategy allowed us to ourselves the mission, vision, policies, objectives and strategies that will allow us through actions reach the proposed objectives with the strategic plan. It identifies the strengths, weaknesses, opportunities and threats, and then enter a process of construction of the scenarios in which they can act the Latin American Educational Center for a third time to define alternative strategies to guide their actions, finally presents the operational plans to be implemented in order to evaluate the results of this proposal. We considered that the main programs of action are: • Training Plan for teachers and administrators. • Workshop for Managers: Strategies for Institutional Dissemination. • Communication Workshop for students. • Parent Workshop School.